2022
DOI: 10.17219/acem/154623
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen suppresses oxidative stress by inhibiting the p38 MAPK signaling pathway in preeclampsia

Abstract: Background. Hypertensive disorders complicating pregnancy (HDCP) are one of the most serious medical disorders during pregnancy.Objectives. To investigate the effects of hydrogen on the mitogen-activated protein kinase (MAPK) signaling pathway in preeclampsia (PE). Materials and methods.The N(omega)-nitro-L-arginine methyl ester (L-NAME)-induced PE model with Sprague Dawley (SD) rats was employed. An inhibitor of MAPK signaling pathways (SB203580) was used as a p38 MAPK inhibitor. The SD rats were randomized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…It might be associated with the hydrogen ion level of chicken embryos. Previous study revealed that the hydrogen ion level cumulated and increased with hatch age for chicken embryos ( Murray and Assistance of Yetta, 1926 ), and another study indicated that the hydrogen-rich saline treatment significantly decreased the p38 MAPK mRNA expression and p-p38 MAPK protein level in the placentas of pregnant rats ( Guo et al, 2023 ). Therefore, the hydrogen ion level increased when the PBS injected into the chick embryos, it significantly decreased the mRNA expression of p38.…”
Section: Discussionmentioning
confidence: 99%
“…It might be associated with the hydrogen ion level of chicken embryos. Previous study revealed that the hydrogen ion level cumulated and increased with hatch age for chicken embryos ( Murray and Assistance of Yetta, 1926 ), and another study indicated that the hydrogen-rich saline treatment significantly decreased the p38 MAPK mRNA expression and p-p38 MAPK protein level in the placentas of pregnant rats ( Guo et al, 2023 ). Therefore, the hydrogen ion level increased when the PBS injected into the chick embryos, it significantly decreased the mRNA expression of p38.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that oxidative and fibrotic bursts are key constituents that fine-tune and transduce the inflammatory response prompted by MAPK signaling. Recent data from studies on cardiorenal injuries suggests that the activation of the pro-oxidant NADPH oxidase following MAPKs phosphorylation results in the upregulation of pro-fibrotic transforming growth factor β1 and extracellular degradation signals regulated by MMPs 49 51 . The latter molecules are necessary for provoking tissue transition from the inflammatory phase to the fibrotic remodeling phase 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%